THE ROLE OF INVERSION TECTONICS IN THE STRUCTURE OF THE CORDILLERA ORIENTAL (NW ARGENTINEAN ANDES) - Carrera N.; Muñoz J.A.; Sàbat F.; Roca E.; Mon R. (My University, 2006)
The Salta Basin of Cretaceous age in the Andes of NW Argentina was inverted during the development of the Cordillera Oriental between the Neogene and Recent. The different orientations of the extensional faults of the Salta Rift System and the subsequent W-E shortening resulted in a great variety of inversion structures. Extensional faults dipping NE to ESE were preferentially reactivated as contractional faults. The initial stepped geometry of these faults gave rise to a distinctive sigmoidal pattern of basement-involved thrusts and related folds. These contractional structures tended to run parallel to the extensional faults and acquired a N-S trend across the previous accommodation zones, resulting in folding interference patterns. Other interference patterns are attributed to the superposition of contractional folds on previous rollovers and to the constrictional deformation imposed by the reactivation of adjacent extensional faults with different orientations. The NNW to WSW dipping extensional faults show no evidence of reactivation despite the fact that some of them are folded. The inversion at crustal scale is limited owing to the presence of the Cretaceous Salta Rift across the different Andean structural units and foreland. © 2006 Elsevier Ltd. All rights reserved.
Keywords: ANDES; ARGENTINA; INVERSION TECTONICS; OBLIQUE INVERSION; Neogene; Cretaceous; Cenozoic::Neogene; Кайнозой::Неоген; Mesozoic::Cretaceous; Мезозой::Меловая